Innovative Research on the Grassroots Cancer Prevention and Control System in China Based on Artificial Intelligence Exploring Technology Empowerment and Standardization Pathways - Yang, Bowen; Mao, Yuanyuan (Journal of Contemporary Medical Practice, 2025)
Under the steady advancement of the “Healthy China 2030” strategy, grassroots cancer prevention and control still face multiple challenges, including a shortage of medical resources, low coverage of health education, insufficient capacity for early cancer screening, and a lack of standardized diagnosis and treatment protocols. To address these challenges, this paper proposes leveraging technology empowerment and optimizing standardization pathways to promote the application of artificial intelligence (AI) in personalized health education, enhance the adoption of early screening technologies, and advance the standardization of diagnosis and treatment. These measures aim to facilitate the sharing of grassroots medical resources and narrow the urban-rural healthcare gap. Future development will focus on precision medicine and personalized treatment, utilizing genetic data and multimodal analysis to develop individualized treatment plans for patients. Additionally, the “unmanned hospital” model will be explored, where AI-driven automation in screening, sample management, and treatment processes is employed to alleviate resource shortages at the grassroots level. This study aims to provide innovative ideas and solutions for improving the grassroots cancer prevention and control system.